Specific inhibitors of HIV capsid assembly binding to the c-terminal domain of the capsid protein: evaluation of 2-arylquinazolines as potential antiviral compounds - Machara, Aleš; Lux, Vanda; Kožíšek, Milan; Grantz Šašková, Klára; Štěpánek, Ondřej; Kotora, Martin; Parkan, Kamil; Pávová, Marcela; Glass, Bärbel; Sehr, Peter; Lewis, Joe; Müller, Barbara; et al. (Journal of medicinal chemistry, 2016)
Assembly of human immunodeficiency virus (HIV-1) represents an attractive target for antiretroviral therapy which is not exploited by currently available drugs. We established high-throughput screening for assembly inhibitors based on competition of small molecules for the binding of a known dodecapeptide assembly inhibitor to the C-terminal domain of HIV-1 CA (capsid). Screening of >70000 compounds from different libraries identified 2-arylquinazolines as low micromolecular inhibitors of HIV-1 capsid assembly. We prepared focused libraries of modified 2-arylquinazolines and tested their capacity to bind HIV-1 CA to compete with the known peptide inhibitor and to prevent the replication of HIV-1 in tissue culture. Some of the compounds showed potent binding to the C-terminal domain of CA and were found to block viral replication at low micromolar concentrations.
Publication date December 21, 2015
Gesehen am 22.05.2020